2020
DOI: 10.1136/bmjgh-2020-002596
|View full text |Cite
|
Sign up to set email alerts
|

The impact of country reimbursement programmes on living kidney donations

Abstract: IntroductionLiving-donor kidney transplantation is the gold standard treatment for patients with end-stage kidney disease. However, potential donors ubiquitously face financial as well as logistical barriers. To remove these disincentives from living kidney donations, the governments of 23 countries have implemented reimbursement programmes that shift the burdens of non-medical costs from donors to the governments or private entities. However, scientific evidence for the effectiveness of these programmes is sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Nevertheless, donors still receive no benefits or social support in Korea. Reimbursement policies for donors may be a practical approach to alleviate kidney shortages [ 25 ]. Recent policies for reimbursement of the economic consequences incurred by donors have emerged mainly in Western countries, including the United States, United Kingdom, and Canada, rather than in Asian countries [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, donors still receive no benefits or social support in Korea. Reimbursement policies for donors may be a practical approach to alleviate kidney shortages [ 25 ]. Recent policies for reimbursement of the economic consequences incurred by donors have emerged mainly in Western countries, including the United States, United Kingdom, and Canada, rather than in Asian countries [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 27 The findings of this study reiterate the ongoing financial concerns among potential donors despite numerous initiatives to combat this issue. Siddique et al 18 looked at 23 countries and found that reimbursement programs increased donation numbers. However, it is possible that existing reimbursement strategies may be further improved.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Numerous barriers exist in the donation process, including health-related concerns, insufficient knowledge about kidney transplant, social circumstances, financial ramifications, and a rigorous screening process. [10][11][12] While many countries around the world have instituted more comprehensive remuneration strategies leading to increased LDKTs, [13][14][15][16][17][18] factors such as gender, culture, or education were not taken into account. There is little research on what actually matters most to potential donors and what supports assist in proceeding with donation.…”
Section: Introductionmentioning
confidence: 99%
“…The debate on increasing organ donation rates by changing policies from an opt-in system (termed ‘explicit consent’) to an opt-out system (termed ‘presumed or deemed consent’) for organ donation is still ongoing. Previous studies have demonstrated that adopting the policy of presumed consent (‘opt-out’) rather than explicit consent (‘opt-in’),6–9 higher socioeconomic status within society (eg, high education level),9–12 high availability of the required infrastructure for transplantation services9 13 and the increased gross domestic product (GDP) per capita and investment in healthcare services9 10 have an influence on successfully realised organ transplantations. While various factors are known to affect organ donation rates, none of these aforementioned studies has investigated the independence of the influence of socioeconomic factors on deceased organ donation rates.…”
Section: Introductionmentioning
confidence: 99%